Does spatial proximity supplant family ties? Exploring the role of neighborly support for older people in diverse, aging cities. Issue 3 (16th March 2022) - Enßle, Friederike; Dirksmeier, Peter; Helbrecht, Ilse
ABSTRACT: The aging population, coupled with increasing diversification, is currently altering the social fabric of cities worldwide. At the local level, social ties within a neighborhood play a key role in enabling older people to age in familiar surroundings. However, family ties in the neighborhood become less common implying that older people become more dependent on alternative support systems such as friends and neighbors. Drawing from a mixed-method research in Berlin (Germany), focus group discussions (26 participants) and survey data ( n = 506), we explore the scope of neighborhood support in later life. Our qualitative findings suggest that women, migrants, and people without families close by primarily provide support to fellow older people. Findings from ordinal regression analysis support this on a larger scale. We conclude that these findings point to a new meaning of spatial proximity for social support in times of weakened family ties and growing diversity in old age.